A comparative study of heat-cured and gamma-cured fiber-reinforced denture-base acrylic resins: Residual monomer and flexural strength. Issue 8 (October 2020) - Ergun, Ece; Ergun, Ümit; Kalıpçılar, Betül
This study was performed to determine and compare the effect of heat and gamma-ray polymerization methods on the residual monomer and flexural strength of polyethylene fiber-reinforced denture-base acrylic resins. Four groups ( n = 10) of specimens of polyethylene fiber-reinforced denture-base material were prepared in the form of thin disks. The first group was subjected to heat-curing and the other three groups were polymerized with gamma irradiation at doses of 15, 25, and 35 kGy, respectively. Fourier-transform infrared (FTIR) spectrometer was used to monitor the corresponding polymerization processes. The analysis of residual monomer was carried out by high-performance liquid chromatography–photodiode array detector. A three-point bending test was used to evaluate the flexural strength of the samples. The one-way analysis of variance test was performed to determine the significant differences between the groups. The absence of the bands related to carbon–carbon double bond in the FTIR spectra of all test groups was an evidence of polymerization. The mean weight percentage of residual monomer was successively ranked from highest to lowest in; heat-cured, gamma-cured at 15–35 kGy. However, no significant difference ( p = 0.462) was found between gamma-cured samples at 25 and 35 kGy. Mechanical test results revealed that heat-cured samples had higher flexural strength than gamma-cured specimens ( p < 0.001). Within the limitations of this study, polymerization with gamma-rays at 15 kGy was proposed as a promising technique in terms of the residual monomer and flexural strength results.